FHL2 regulates the resolution of tissue damage in chronic inflammatory arthritis. Issue 12 (14th August 2014) - Wixler, Viktor; Cromme, Christoph; Retser, Eugen; Meyer, Lars-Henrik; Smyth, Neil; Mühlenberg, Katja; Korb-Pap, Adelheid; Koers-Wunrau, Christina; Sotsios, Yannis; Bassel-Duby, Rhonda; Baeten, Dominique; Tak, Paul P; et al.
Abstract : Objective: We analysed the role of the adaptor molecule four-and-a-half Lin11, Isl-1 & Mec-3 (LIM) domain protein 2 (FHL2) in the activation of fibroblast-like synoviocytes in human rheumatoid arthritis (RA) and tumour necrosis factor α (TNFα)-dependent animal models of the disease. Methods: Synovial tissues of patients with RA and osteoarthritis (OA) as well as hind paw sections from arthritic human TNFα transgenic (hTNFtg) mice and synovial fibroblasts from these were analysed. The effects of cytokines on the expression of FHL2 and disease-relevant matrixmetalloproteases (MMPs) were determined. Analyses of human tissue specimens from patients treated with anti-TNFα as well as anti-TNFα treatment of hTNFtg mice were performed to substantiate the TNFα effects on FHL2 levels. FHL2 −/− mice and hTNFtg mice (with constitutive or inducible transgene expression) were crossbred to generate TNFα overexpressing FHL2-deficient animals. Signalling pathways were analysed in cells from these mice and in human cells after knock down of FHL2 by western blot. Results: FHL2 levels were higher in RA than in OA and in hTNFtg than in wild-type mice. Surprisingly, while transforming growth factor (TGF)β-induced FHL2 expression, TNFα suppressed FHL2. In vivo, anti-TNFα treatment led to higher FHL2 levels both in RA patients and hTNFtg mice. The loss of FHL2 increased joint destruction in hTNFtg mice, which was accompanied by elevated MMP-13. In vitro, TNFα-mediated MMP-13 was significantly higher in FHL2 −/− cells and after knock down of FHL2, which was caused by prolonged p38 MAPK activation. Conclusions: These data suggest that FHL2 serves as a protective factor and that, rather than promoting the pathology, the upregulation of FHL2 in RA occurs in frame of a regenerative attempt.